Acceptability of Fibreboard Carton Boxes for Tomato Packaging in Nigerian Retail Markets: A Case Study of Mile 12 Market, Lagos - BABARINSA, OLUMUYIWA ADEKANMI; Babarinsa, Ibijoke Itunu; Ogundele, Richard Babatunde; Babarinsa, Folorunso Adekunle (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Nigeria, one of Africa's leading tomato producers, faces substantial postharvest losses due to inadequate packaging methods, with losses estimated at 20% to 50% of total production. Traditional packaging methods, such as raffia baskets and nylon sacks, are prevalent due to their low cost but offer insufficient protection against mechanical damage and spoilage. This study investigates the acceptability of fibreboard carton boxes as a sustainable and efficient packaging alternative among tomato retailers at Mile 12 Market, Lagos, Nigeria. Using a structured questionnaire, data were collected from 80 retailers on their demographic profiles, current packaging practices, and perceptions of fibreboard carton boxes. Descriptive statistical analysis revealed that while 55.6% of respondents were aware of fibreboard carton boxes, traditional packaging methods were prevalent. All respondents (100%) recognized the need for improved packaging to minimize losses, with 55.6% viewing fibreboard carton boxes as viable. Key barriers to adoption included scepticism about cost and durability, though preferences for varied box sizes and distribution channels indicated flexibility in implementation. Adoption will require targeted awareness campaigns, stakeholder engagement, and alignment with existing market structures. Future research should focus on cost-benefit analysis and scalability of fibreboard carton boxes in Nigeria’s agricultural value chain.